Human Behavior in an Emerging Totalitarian Society - Morris, G. Barry (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper, in viewing the spread of totalitarian regimes since World War II, suggests that the Western world may be already embedded with the essential ingredients leading to totalitarianism. Since normal behavior is often perceived in terms of the existing traditions, attitudes, customs and values of the society inwhich it is observed, a "new society" would promote new perspectives of human behavior and a new concept of psychological health. In a totalitarian society the self-actualizing individual might be seen to be eliciting unproductive and unacceptable behavior, and a new measure of normality congruent with new political structures might evolve.